2014
DOI: 10.13110/humanbiology.86.3.0185
|View full text |Cite
|
Sign up to set email alerts
|

A Homogenizing Process of Selection Has Maintained an “Ultra-Slow” Acetylation <em>NAT2</em> Variant in Humans

Abstract: homogenizing process of selection has maintained an 'ultra-slow' acetylation NAT2 variant in humans" (2014

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 47 publications
2
13
1
Order By: Relevance
“…Regarding the possible implication of gene polymorphisms related with activation or detoxification mechanisms, several studies, including recent meta-analyses, have shown a slight but significant increased risk for PD in Caucasian related with certain polymorphisms in the CYP2D6 [77], GSTM1 [78], and GSTT1 [79] genes, as well as with genes related to oxidative stress [80][81][82]. According with the results of the present systematic review and meta-analysis, NAT2 polymorphisms do not seem to be a major determinant for the risk of developing PD in Caucasian individuals (a human population characterized by a high frequency of slow acetylators), but are clearly associated with the risk in Oriental subjects which, probably due to adaptive evolution [83], show a extremely low frequency of slow acetylators. Because of the large inter-ethnic variability in NAT2 allele frequencies, it cannot be ruled out that the putative association shown in some individual studies could be ethnic-specific, that is, relevant for certain human populations only.…”
Section: Expert Opinionsupporting
confidence: 55%
“…Regarding the possible implication of gene polymorphisms related with activation or detoxification mechanisms, several studies, including recent meta-analyses, have shown a slight but significant increased risk for PD in Caucasian related with certain polymorphisms in the CYP2D6 [77], GSTM1 [78], and GSTT1 [79] genes, as well as with genes related to oxidative stress [80][81][82]. According with the results of the present systematic review and meta-analysis, NAT2 polymorphisms do not seem to be a major determinant for the risk of developing PD in Caucasian individuals (a human population characterized by a high frequency of slow acetylators), but are clearly associated with the risk in Oriental subjects which, probably due to adaptive evolution [83], show a extremely low frequency of slow acetylators. Because of the large inter-ethnic variability in NAT2 allele frequencies, it cannot be ruled out that the putative association shown in some individual studies could be ethnic-specific, that is, relevant for certain human populations only.…”
Section: Expert Opinionsupporting
confidence: 55%
“…However, because the distribution of NAT2 molecular diversity does not match the expected population structure observed at neutral genomic loci, and alternative explanation invoking a process of selection on standing variation is favoured at present. This hypothesis holds that a slower acetylation phenotype became advantageous in the new dietary environments of food‐producing populations, so that pre‐existing alleles conferring a slow enzymatic activity, which were kept at low frequencies through purifying selection, would have become simultaneously positively selected in populations adopting agriculture or animal herding …”
Section: Genetic Evidence On Sahelian Populationsmentioning
confidence: 99%
“…This hypothesis holds that a slower acetylation phenotype became advantageous in the new dietary environments of food-producing populations, so that pre-existing alleles conferring a slow enzymatic activity, which were kept at low frequencies through purifying selection, would have become simultaneously positively selected in populations adopting agriculture or animal herding. 95 A study 96 analysing the genetic structure of human populations living either in the Sahel belt or in surrounding African ecosystems showed that the predicted prevalence of NAT2 slow acetylation is significantly higher among pastoralists than among farmers in those regions, but also among populations living in the Sahel/Savannah belt than among those living in humid tropical and equatorial zones, irrespective of their lifestyle. Two alternative hypotheses have been proposed, both of which invoke selective pressures acting on the evolution of this specific gene (due to the dietary or the chemical environment, respectively).…”
Section: Arylamine N-acetyltransferasementioning
confidence: 99%
“…The NAT2*6 signature polymorphism has been reported to confer an ultra-slow acetylator phenotype [88, 89], and this could explain the higher risk of INH-induced hepatotoxicity in slow acetylators carrying this particular SNP. A slow acetylator haplotype composed of rs4646244 (NM_00015.2:c.-1144T>A) allele A, rs4646267 (NM_000015.2:c.-949A>G) allele A, rs1799930 allele A, and rs1799931 (NM_000015.2:c.857G>A, signature SNP for the NAT2*7 allelic group) allele G, has been associated with an increased risk of hepatotoxicity.…”
Section: Pharmacogeneticsmentioning
confidence: 99%